KEBIJAKAN PENGENTASAN KEMISKINAN DI DESA ERAN BATU - Widianti; Dema, Herman; Jabbar, Abdul (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to investigate the local government's policies in reducing poverty levels in Eran Batu Village and to identify the factors contributing to the high poverty rate in the village. The research method applied is qualitative, where data sources are obtained through observation, interviews, and documentation processes. Data analysis is conducted through stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that out of seven efforts implemented by the local government in Eran Batu Village, only one assistance program failed to be executed despite multiple submissions, namely the program for rehabilitating uninhabitable houses. Factors contributing to the high poverty rate in Eran Batu Village include community concerns in obtaining capital and the low level of Human Resources (HR).